2020
DOI: 10.20944/preprints202012.0112.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Hypoxia-Inducible Factor Post-Translational Modifications in Regulating its Localisation, Stability and Activity

Abstract: The hypoxia signalling pathway enables adaptation of cells to decreased oxygen availability. When oxygen becomes limiting, the central transcription factors of the pathway, hypoxia-inducible factors (HIFs), are stabilised and activated to induce the expression of hypoxia-regulated genes, thereby maintaining cellular homeostasis. Whilst hydroxylation has been thoroughly described as the major and canonical modification of the HIF-α subunits, regulating both HIF stability and activity, a range of other… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 116 publications
(141 reference statements)
0
0
0
Order By: Relevance
“…Surprisingly, even though there is ample evidence for an important role of HIF-1α induction during infection with various Leishmania species (Alonso et al, 2019;Arrais-Silva et al, 2005;Hammami et al, 2017;Hammami et al, 2015;Mesquita et al, 2020;Rocha et al, 2018;Weinkopff et al, 2019), expression and protein abundance of this TF were neither altered in ivLIMs nor evLIMs, suggesting alternative forms of regulation. While we cannot rule out possible post-translational modifications that may alter HIF1-α TF activity (Albanese et al, 2020), we identified the m 6 A reader protein IGF2BP2 as a possible key regulator underlying HIF-1α-independent LIMs metabolic reprogramming. This mRNA-binding protein is known to control glycolytic metabolisms by stabilizing various transcripts of the glycolytic pathway, including m 6 A modified Ldha, AldoA or Hk2 transcripts (Liu et al, 2021;Wu et al, 2023;Zhou et al, 2024).…”
Section: Discussionmentioning
confidence: 83%
“…Surprisingly, even though there is ample evidence for an important role of HIF-1α induction during infection with various Leishmania species (Alonso et al, 2019;Arrais-Silva et al, 2005;Hammami et al, 2017;Hammami et al, 2015;Mesquita et al, 2020;Rocha et al, 2018;Weinkopff et al, 2019), expression and protein abundance of this TF were neither altered in ivLIMs nor evLIMs, suggesting alternative forms of regulation. While we cannot rule out possible post-translational modifications that may alter HIF1-α TF activity (Albanese et al, 2020), we identified the m 6 A reader protein IGF2BP2 as a possible key regulator underlying HIF-1α-independent LIMs metabolic reprogramming. This mRNA-binding protein is known to control glycolytic metabolisms by stabilizing various transcripts of the glycolytic pathway, including m 6 A modified Ldha, AldoA or Hk2 transcripts (Liu et al, 2021;Wu et al, 2023;Zhou et al, 2024).…”
Section: Discussionmentioning
confidence: 83%